2012
DOI: 10.1158/0008-5472.can-12-0908
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Variation in Murine Natural Killer Gene Complex Contributes to Differences in Immunosurveillance for Urethane-Induced Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related deaths worldwide and results from a complex interaction between carcinogen exposure and inherent susceptibility. Despite its prevalence genetic factors that predispose to the development of lung cancer remain elusive. Inbred mouse models offer a unique and clinically relevant tool to study genetic factors that contribute to lung carcinogenesis due to the development of tumors that resemble human adenocarcinoma and broad strain-specific v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…Based on these results, we assumed that ptaquiloside suppressed NK cell-mediated cytotoxicity even at lower doses, contributing to the greater number of lung adenomas that was observed in the PU group. The results of our study corroborate the results of a recent study that was conducted by Kreisel et al 36 , which indicated that only the suppression of NK cell activity contributes to increase the incidence of urethane-induced lung lesions in the C57BL/ 6 mouse strain, which was the same strain that was used in this study. In addition, the results of this study indicated that C57BL/6 Rag À/À and C57BL/6 athymic nu/nu (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on these results, we assumed that ptaquiloside suppressed NK cell-mediated cytotoxicity even at lower doses, contributing to the greater number of lung adenomas that was observed in the PU group. The results of our study corroborate the results of a recent study that was conducted by Kreisel et al 36 , which indicated that only the suppression of NK cell activity contributes to increase the incidence of urethane-induced lung lesions in the C57BL/ 6 mouse strain, which was the same strain that was used in this study. In addition, the results of this study indicated that C57BL/6 Rag À/À and C57BL/6 athymic nu/nu (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the results of this study indicated that C57BL/6 Rag À/À and C57BL/6 athymic nu/nu (i.e. mice without T and NKT lymphocytes) had the same sensitivity as the C57BL/6 wild-type mice to the effects of urethane 36 . Thus, we can conclude that the effects of urethane on the maturation of T lymphocytes that were observed in this study did not contribute to the increases in lung adenomas.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Corroborating our hypothesis here, a recent study conducted by Kreisel et al (2012) indicated that only the suppression of NK cell activity contributes to an increase in incidence of urethaneinduced lung lesions in the C57BL/6 mouse strain, the strain used here. Furthermore, an association was also demonstrated between suppression of NK cell activities and a higher risk of developing head and neck cancers in humans, as well as with a higher incidence of 3-methylcholanthrene-induced sarcomas in mice (Accomando et al, 2012;O'Sullivan et al, 2012).…”
Section: Discussionsupporting
confidence: 84%